BERBAGAI ALTERNATIF MODEL DAN PENDEKATAN DALAM PEMBELAJARAN MATEMATIKA - Didik Sugeng Pambudi (Jurnal Pendidikan Matematika, 2007)
The poor quality of mathematics learning process is a factor influence the low of mathematics students’ achievement, where there are still many teachers using a conventional teaching method at school. This results in students’ failure to learn the subject. Therefore, the teachers should apply some models and approach of mathematics learning which hopefully can improve the quality of mathematics education in Indonesia. Keywords : Mathematics Learning Process, Mathematics Learning Models and Approach